2004
DOI: 10.1111/j.0019-2805.2004.01847.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylenedioxymethamphetamine (MDMA, ‘Ecstasy’): a stressor on the immune system

Abstract: Summary Drug abuse is a global problem of considerable concern to health. One such health concern stems from the fact that many drugs of abuse have immunosuppressive actions and consequently have the potential to increase susceptibility to infectious disease. This article is focused on the impact of the amphetamine derivative, methylenedioxymethamphetamine (MDMA; ‘Ecstasy’) on immunity. Research conducted over the last 5 years, in both laboratory animals and humans, has demonstrated that MDMA has immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 73 publications
(138 reference statements)
2
28
0
3
Order By: Relevance
“…B cells are main mediators in the humoral immune response but they also are important antigen-presenting cells for exogenous proteins. Our present results suggest that chronic AMPH severely compromised humoral immune responses against both T-dependent and T-independent antigens, and could explain the enhanced vulnerability to several infectious diseases observed in drug addicts (1,3). Antibodies are the main adaptative mechanism of defence against bacterial infections, and also play an important role in the defence against other types of pathogens.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…B cells are main mediators in the humoral immune response but they also are important antigen-presenting cells for exogenous proteins. Our present results suggest that chronic AMPH severely compromised humoral immune responses against both T-dependent and T-independent antigens, and could explain the enhanced vulnerability to several infectious diseases observed in drug addicts (1,3). Antibodies are the main adaptative mechanism of defence against bacterial infections, and also play an important role in the defence against other types of pathogens.…”
Section: Discussionmentioning
confidence: 64%
“…Lymphopenia as well as the increase in circulating granulocyte number, granulocytosis, have been also found in mice following chronically injecting AMPH (10), in rats following MDMA administration (5), in both laboratory animals and humans MDMA consumers (3) and in rats following acute AMPH administration (12). However no difference neither in total leukocyte count nor the percentage of T-lymphocytes in AMPHtreated animals was observed by other authors (1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that MDMA increases susceptibility to infectious diseases in humans [13,14,15] and in laboratory animals [16,17]. Moreover, MDMA was shown to suppress the generation of lipopolysaccharide-induced proinflammatory cytokines such as tumor necrosis factor-α and interleukin (IL)-1β [18,19] and to increase the lipopolysaccharide-induced production of the anti-inflammatory cytokine IL-10 [20].…”
Section: Introductionmentioning
confidence: 99%